ANALISIS PENGARUH FAKTOR LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN POLITEKNIK NEGERI MALANG - Mahmudatul Himma (Adbis: Jurnal Administrasi dan Bisnis, 2017)
This research was aimed at 1) Knowing and analyzing the influence of work environment to performance of an employee simultaneously 2) Knowing and analyzing the influence of work environment to performance of an employee partially. The number of sample there are 46 employees of State Polytechnic of Malang. Purposive sampling was used in determining the sampling and Likert scale. The tools analysis used multiple regression analysis. The result of study showed that work environment, effect both of simultaneously and partially toward performance of an employee